Masjid Wakaf dan Transformasi Sosial Umat di Masjid Besar Imam Ulomo Sampung Ponorogo - Huda, Miftahul; Santoso, Lukman (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2017)
Great Mosque Imam Ulomo Sampung Ponorogo is a waqf mosque located in the countryside. Making the mosque as a partner devotion is ikhtiyar Masjid realize that far from urban areas and are in the corners to not only as a religious social center but also pursued into the mosque advanced and progressive socio-economic and even become an example for others in the interior of the mosque. Based on the above discussion, this article examines Waqf Masjid and Social Transformation of People in the Great Mosque of Imam Ulomo Sampung Ponorogo. The aim of this devotion as an Islamic community development efforts related to change management model endowments, from traditional to professional. Based on the study, it can be concluded: First, performing well through socialization and training paradigm of governance productive endowments. Second, institutional strengthening training nadzir endowments. This activity is very beneficial to the development and improvement of governance endowments productive in society, in particular institutional waqf mosque.